PARADIGMA ILMU PENGETAHUAN DAN IMAN DALAM PERISTIWA ISRO’MI’RAJ NABI MUHAMMAD SAW - Takdir Alisyahbana (El-Ghiroh : Jurnal Studi Keislaman, 2018)
Isro 'and mi'raj the greatest and furthest ride beyond the seventh heaven of "Sidratil Muntaha" performed by the Prophet Muhammad, within eight hours of the night, the 27th of Rajab in the tenth year of prophethood. Isro 'mi'raj accelerated the inaugural form of Muhammad SAW as the last Messenger and Prophet. Isro 'and mi'raj of the Holy Prophet, is phenomenal and occurs once throughout the history of mankind, therefore various opinions emerged from the time of the Prophet to the era of 21st century degortization. Various theories of science trying to analyze such a powerful event, certainly never satisfying.Karsa imanlah who is able to answer the truth of Isro 'and Mi'raj Prophet Muhammad, which resulted in the obligation to pray five times.